Differential Lung Ventilation Using a Bronchial Blocker in a Pediatric Patient on Extracorporeal Membrane Oxygenation: A Case Report. Issue 6 (15th September 2019) - Bhargava, Vidit; Arastu, Ali; Darling, Curtis; Wang, Ellen; Kache, Saraswati
Abstract : We describe a patient with acute on chronic respiratory failure after a cardiac arrest who was cannulated to venoarterial extracorporeal membrane oxygenation. The patient developed right-sided interstitial emphysema with air leak and left-sided hemothorax with secondary atelectasis. A differential lung ventilation strategy was used in which an endotracheal tube was placed in the left main stem bronchus and a bronchial blocker was placed in the right mainstem bronchus. The patient's overall pulmonary function improved, and he was successfully decannulated from extracorporeal membrane oxygenation. In conclusion, differential lung ventilation may be performed in patients on extracorporeal membrane oxygenation with disparate lung disease as an alternative ventilation strategy.